2022
DOI: 10.1177/1934578x221144579
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products as Cancer Chemo Preventive Agents: Where We Stand

Abstract: This work briefly reviews cancer chemoprevention. This is a very challenging field, as products with a high level of toxicity such as chemotherapeutic agents may be proposed and accepted only under life-threatening conditions. Cancer chemoprevention is otherwise limited to completely safe substances, preferably having neither toxic nor side effects, administered in relatively low amounts. Phases of clinical trials, therapeutic end-points, and biomarkers of chemoprevention are difficult to be defined. The clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Phytochemicals such as resveratrol and curcumin have been investigated for their potential as chemoprotective agents (Boretti, 2022;Xiao et al, 2018). However, most studies were preclinical since clinical trials gave negative or null results (Boretti, 2022). Findings of the present study pave the way for future inquiries to increase our understanding of this plant mixture's chemoprotective mechanism of action.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Phytochemicals such as resveratrol and curcumin have been investigated for their potential as chemoprotective agents (Boretti, 2022;Xiao et al, 2018). However, most studies were preclinical since clinical trials gave negative or null results (Boretti, 2022). Findings of the present study pave the way for future inquiries to increase our understanding of this plant mixture's chemoprotective mechanism of action.…”
Section: Discussionmentioning
confidence: 82%
“…Many preclinical reports have been dedicated to the chemopreventive effect of phytochemical compounds. Phytochemicals such as resveratrol and curcumin have been investigated for their potential as chemoprotective agents (Boretti, 2022;Xiao et al, 2018). However, most studies were preclinical since clinical trials gave negative or null results (Boretti, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The widespread belief that these compounds help prevent cancer by reducing free radicals has led to a surge in their use in developed nations [3]. Additional research conducted in separate labs has demonstrated that most of these compounds can trigger cell death by apoptosis, inhibit antiapoptotic pathways, halt cell proliferation, and alter several critical proteins involved in cancer cell growth [4]. Although they have shown anticancer effects in both laboratory and animal studies, no specific mechanism has been identified to explain these effects.…”
mentioning
confidence: 99%
“…In the last few years, many natural products and their derivatives have been explored as cytotoxic, antiproliferative or antioxidant agents and have also shown antitumor effects in preclinical and clinical research ( Boretti, 2022 ). In comparison to synthetic medications, natural compounds have a higher amount of stiffness, which enhances protein cross-talk.…”
mentioning
confidence: 99%